Measuring changes in self-concept: a qualitative evaluation of outcome questionnaires in people having acupuncture for their chronic health problems - Paterson, Charlotte (BioMed Central, 2006)
BACKGROUND: Changes in self-concept are an important potential outcome for many interventions for people with long-term conditions. This study sought to identify and evaluate outcome questionnaires suitable for quantifying changes in self-concept in people with long-term conditions, in the context of treatment with acupuncture and Chinese medicine. METHODS: A literature search was followed by an evaluation of three questionnaires: The Wellbeing Questionnaire W-BQ12, the Patient Enablement Instrument (PEI), and the Arizona Integrative Outcome Scale (AIOS). A convenience sample of 23 people completed the questionnaires on two occasions and were interviewed about their experience and their questionnaire responses. All acupuncturists were interviewed. RESULTS: Changes in self-concept were common and emerged over time. The three questionnaires had different strengths and weaknesses in relation to measuring changes in self-concept. The generic AIOS had face validity and was sensitive to changes in self-concept over time, but it lacked specificity. The PEI was sensitive and specific in measuring these changes but had lower acceptability. The sensitivity of the W-BQ12 was affected by initial high scores (ceiling effect) and a shorter timescale but was acceptable and is suitable for repeated administration. The PEI and W-BQ12 questionnaires worked well in combination. CONCLUSION: Changes in self-concept are important outcomes of complex interventions for people with long-term illness and their measurement requires carefully evaluated tools and long-term follow-up. The literature review and the analysis of the strengths and weaknesses of the questionnaires is a resource for other researchers. The W-BQ12 and the PEI both proved useful for this population and a larger quantitative study is planned.